Oskar protein interaction with Vasa represents an essential step in polar granule asssembly. - Breitwieser, W.; Markussen, F.H.; Horstmann, H.; Ephrussi, A. (Genes & Development, 1996)
The posterior pole plasm of the Drosophila egg contains the determinants of abdominal and germ-cell fates of the embryo. Pole plasm assembly is induced by oskar RNA localized to the posterior pole of the oocyte. Genetics has revealed three additional genes, staufen, vasa, and tudor, that are also essential for pole plasm formation. Staufen protein is required for both oskar RNA localization and translation. Vasa and Tudor are localized dependent on Oskar protein and are required to accumulate Oskar protein stably at the posterior pole. We have explored interactions between these gene products at the molecular level and find that Oskar interacts directly with Vasa and Staufen, in a yeast two-hybrid assay. These interactions also occur in vitro and are affected by mutations in Oskar that abolish pole plasm formation in vivo. Finally, we show that in the pole plasm, Oskar protein, like Vasa and Tudor, is a component of polar granules, the germ-line-specific RNP structures. These results suggest that the Oskar-Vasa interaction constitutes an initial step in polar granule assembly. In addition, we discuss the possible biological role of the Oskar-Staufen interaction.